Impact of Population Income on the Number of Forest Fires: a Case Study; International Review on Modelling and Simulations (IREMOS); Vol. 15, № 1 - Bazarova O. V. Oyuna Vladimirovna; Bazarov A. V. Aleksandr Vladimirovich; Baranovskiy N. V. Nikolay Viktorovich; Sychev R. S. Roman Sergeevich; Atutov E. B. Evgeniy Borisovich (2022, 2022)
Title screen